(untitled) (MAUSAM, 2016)
Temporal changes in the monthly and seasonal temperatures over Varanasi District were analysed, based on the 40 years of time series databases of daily temperatures from 1971 to 2010. The temperature changes during the two tricades of 1971-2000 and 1981-2010 and also for four decades starting from 1971 to 2010 were investigated and both the Mann–Kendall (MK) trend test and simple linear regression analyses were employed to detect trends in the mean maximum temperatures and mean minimum temperatures. Various extreme temperatures criteria, as well as their corresponding frequencies, were chosen to explore the trends of extreme climate change over Varanasi. The warming of seasonal mean temperature is mainly attributed to changes in the minimum temperature, particularly during the last three decades. A pre-monsoon cooling and its association with increase in heat wave days suggest that, alongwith large-scale circulation, regional and local factors may have played a vital role in influencing the observed climate in the studied area.